ANALISIS PENGARUH PERSAINGAN TERHADAP AGENCY COST (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2010-2012) - Prawibowo, Teguh; Juliarto, Agung (Diponegoro Journal of Accounting, 2014)
The objective of this research is to analyze the effect of competition on agency cost. In this research, the competition is proxied by PPE (Property, Plant, and Equipment), CPS (Cost per Sale), and Company’s Sales while agency cost is proxied by audit fee. This research is based on previous research conducted by Nayeri and Salehi (2013) and Valipour et.al. (2013).The sample of this research was manufacturing company which listed on the Indonesian Stock Exchange (BEI) in the year 2010 to 2012. Data were collected by using purposive sampling method and 131 observation data were analyzed. The hypothesis testing of this research utilized multiple regression analysis with SPSS realease 20.The results of multiple regression analysis show that the PPE (Property, Plant, and Equipment) has no significant effect on audit fees. Meanwhile, CPS (Cost per Sale) has significant negative effect on audit fees and Company’s Sales has significant positive effect on audit fees. The results indicate that competition can mitigates agency cost.